2018
DOI: 10.1103/physrevb.98.174416
|View full text |Cite
|
Sign up to set email alerts
|

Multiferroic phase diagram of E -type RMnO3 films studied by neutron and x-ray diffraction

Abstract: We present a generalized multiferroic phase diagram for orthorhombic RMnO 3 (R = Gd-Lu) based on coherently grown thin films. The magnetic order was identified by neutron-diffraction and resonant soft x-ray scattering experiments. For large R-ions (R = Gd-Dy), the transition temperature to a long-range ordered antiferromagnetic phase is only weakly dependent on the R-ion radius, but decreases monotonically with decreasing R-ion radius for films with R = Ho-Lu. The antiferromagnetic phase is characterized by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The sample was mounted in a He-flow cryostat with the (00l ) − (0k0) crystal axis in the horizontal scattering plane. This geometry gives access to the strongest magnetic peaks (0 q 1) and (0 1 + q 1) for the ICM and CM magnetic order as observed for similar films [9].…”
Section: Samples and Characterizationmentioning
confidence: 69%
See 2 more Smart Citations
“…The sample was mounted in a He-flow cryostat with the (00l ) − (0k0) crystal axis in the horizontal scattering plane. This geometry gives access to the strongest magnetic peaks (0 q 1) and (0 1 + q 1) for the ICM and CM magnetic order as observed for similar films [9].…”
Section: Samples and Characterizationmentioning
confidence: 69%
“…Recently, it was reported that o − RMnO 3 when grown as thin epitaxially strained films show unique changes in multiferroic properties [5,6,9]. At low temperatures the magnetic ground state is characterized by a CM E-type and a large ferroelectric polarization along the a-axis independent of the R-ion radii.…”
Section: A Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to explain the origin of the magnetically induced ferroelectricity, a large number of theoretical models were proposed one after another, such as reverse Dzyaloshinskii-Moriya (D-M) interaction [12], spin-dependent p-d hybridization and exchange striction mechanism [13,14]. So far, numerous single-phase multiferroic materials have been found, such as (Y, Sr, Gd, Dy, Tb, Ho, Lu)MnO 3 films [15][16][17][18], (Dy, Gd, Tb, Ho, Er, Lu)CrO 3 films [19][20][21][22][23], (Gd, Dy, Yb)FeO 3 films [24][25][26], EuTiO 3 films [27], hexaferrite Ba 2−x Sr x Mg 2 Fe 12 O 22 single crystal [28], and LaFeO 3 polycrystal [29]. Despite rich characteristics and fascinating physics, the low working temperature and weak saturation magnetization (M s ) restrict the practical applications of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…The interplay between structure and magnetism can be changed using structural distortions. Here we highlight that ferroelectricity was achieved below 30 and 75 K on orthorhombic GMO thin-films with 10 and 110 nm, deposited by pulsed laser deposition onto (010)-YAlO3 and (001)-SrTiO3 substrates, respectively [9,10]. Recently, the study of epitaxially strained GMO thin-films deposited on (001)-SrTiO3 substrate by RF magnetron sputtering, conveyed an unprecedently reported tetragonal structure at room temperature and ferroelectric below 32 K, up to 35 nm thick films [11].…”
Section: Introductionmentioning
confidence: 82%